2010
DOI: 10.1029/2010jb000865
|View full text |Cite
|
Sign up to set email alerts
|

Low‐temperature magnetism of synthetic Fe‐Ti oxide assemblages

Abstract: [1] Low-T magnetometry (<300 K) is increasingly used to identify magnetic mineral assemblages. The present work aims at establishing a robust data basis for the characterization of polycrystalline synthetic Fe-Ti oxide assemblages from low-T magnetic measurements. The two-phase samples contained ilmenite-hematite solid solutions (ilmenite ss ) with compositions near to the ilmenite end-member (X Ilm > 0.69), that coexisted either with titanomagnetites or with pseudobrookite ss of intermediate to Ti-rich compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 74 publications
4
15
0
Order By: Relevance
“…Some samples showed a decrease of IRM at 240 K during cooling ( Figure 5). The Verwey transition of magnetite was recognized in most of the samples that showed the decrease at 240 K. The origin of this change is not clear, but a similar magnetization loss at a somewhat lower temperature, 210 K, has been reported for titanomagnetite in the literature [Garming et al, 2007;Engelmann et al, 2010]. Garming et al [2007] observed a decrease at 210 K HIGHLY MAGNETIZED HYDROTHERMAL DEPOSIT in the IRM imparted to magnetic mineral extracts from marine sediments in a strongly reducing environment, and explained the phenomenon by magnetostatic interactions at intergrowths of titanohematite lamellae with titanomagnetite relics.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Some samples showed a decrease of IRM at 240 K during cooling ( Figure 5). The Verwey transition of magnetite was recognized in most of the samples that showed the decrease at 240 K. The origin of this change is not clear, but a similar magnetization loss at a somewhat lower temperature, 210 K, has been reported for titanomagnetite in the literature [Garming et al, 2007;Engelmann et al, 2010]. Garming et al [2007] observed a decrease at 210 K HIGHLY MAGNETIZED HYDROTHERMAL DEPOSIT in the IRM imparted to magnetic mineral extracts from marine sediments in a strongly reducing environment, and explained the phenomenon by magnetostatic interactions at intergrowths of titanohematite lamellae with titanomagnetite relics.…”
Section: Resultssupporting
confidence: 64%
“…A few samples showed more gradual magnetization changes at somewhat lower temperatures (100 K). Titanium substitution is likely to be responsible for this phenomenon [Honig, 1995;Carter-Stiglitz et al, 2006;Engelmann et al, 2010]. The occurrence of pyrrhotite was recognized from similar magnetization changes at 35 K [Rochette et al, 1990] (Figure 5b).…”
Section: Resultsmentioning
confidence: 81%
“…The low‐temperature measurements were made on a Quantum Designs MPMS at frequencies between 1 and 1000 Hz; for clarity we show here (Figure ) only the 1 Hz data. Generally the low‐ T susceptibility has a temperature dependence similar to those of synthetic titanomagnetites with x near 0.3 [ Moskowitz et al ., ; Carter‐Stiglitz et al ., ; Engelmann et al ., ], with a very strong increase on warming, especially below about −120°C. In addition, a small but sharp drop just below 0°C indicates the presence of a phase in the hematite‐ilmenite solid‐solution series with a composition of 0.75 < y < 0.8 (75–80% mole fraction of ilmenite) [ Lagroix et al ., ; Burton et al ., ; Engelmann et al ., ], and two stable (reversible) high‐ T C phases are evident, a Ti‐poor titanomagnetite (540°C) and nearly pure magnetite (580°C).…”
Section: Thermomagnetic Behavior and Irreversibilitymentioning
confidence: 99%
“…In the case of Ilm ss , however, the χ ‐T curves are not so clearly affected by shifts in composition due to surficial oxidation. The peaks generated by Ilm ss in the temperature‐dependent in‐phase AC susceptibility curves often present a relatively smooth flank on their high‐temperature side, with a drop in susceptibility over 30 to 50 K, even if the crystals have perfectly homogeneous compositions (Figure 7a) [see also Engelmann et al , 2010, Figures 6 and 7]. For samples that also contain more Fe‐rich Ilm ss with exsolution lamellae of Psb ss due to surficial oxidation during EQ, the χ ‐T peaks for Ilm ss show similar gradual drop of the susceptibility over 30 to 50 K (Figure 7b).…”
Section: Effects Of Oxyexsolutions On Thermomagnetic Curvesmentioning
confidence: 99%